Early Diagnosis and Follow-Up of Spontaneous Heterotopic Pregnancy - EV, Acko-Ohui; N’goran; AN, Konan; A, Setcheou; Aubin, Lia Whiva; Anne-Marie, N’goan-Domoua; AV, Konan (Asian Journal of Medical Radiological Research, 2018)
Heterotopic pregnancy is the coexistence of intrauterine pregnancy (IUP) and ectopic pregnancy (EP) in the same patient regardless of the location of the EP. It is a rare but not exceptional pathology whose diagnosis, based on ultrasound, is often difficult. This results in a late discovery involving the patient’s vital prognosis. We report a case of a spontaneous heterotopic pregnancy that occurred in a 26-year-old patient, in whom early ultrasound diagnosis and early management helped to preserve the intrauterine pregnancy that was followed up to the eventual delivery of a eutrophic new-born in apparent good health. Our objective is to recall the existence of this pathology and to contribute to its early diagnosis through the proposal of 3 diagnostic keys.